Jesus and the father : modern evangelicals reinvent the doctrine of the Trinity - Giles, Kevin, 1940- (Grand Rapids, MI : Zondervan, 2006)
Publisher description: The doctrine of the Trinity is one of the cornerstones of Christianity. In Jesus and the Father, Kevin Giles wrestles with questions about the Trinity that are dividing the evangelical community: What is the error called "subordinationism"? Is the Son eternally subordinated to the Father in function? Are the Father and the Son divided or undivided in power and authority? Is the Father-Son-Spirit relationship ordered hierarchical or horizontal? How should the Father and the Son be differentiated to avoid the errors of modalism and subordinationism? What is the relationship between the so-called economic Trinity and the immanent Trinity? Does the Father-Son relationship in the Trinity prescribe male-female relationships in the home and the church? "Kevin Giles points out serious problems in the teaching that the Son is eternally subordinated to the Father and argues effectively for the full eternal equality within the Trinity. This book should be read by all who wrestle with the complex but crucial doctrine of the Trinity."--Millard Erickson, author, Christian Theology "By showing that subordinationism is a revival of a heresy that was systematically rejected by the non-Arian Church, the author reinstates the classical orthodox doctrine of the Trinity in all its scriptural majesty and grandeur."--Gilbert Bilezikian, professor emeritus, Wheaton College "Giles skillfully places before us the stark choice which each generation of theologians must face: will we allow the Bible to speak its message about the Father, Son, and Holy Spirit to us, or will we use the Bible to advance our own agenda? This important book deserves to be widely read and carefully considered."--Paul D. Molnar, professor of systematic theology, St. John's University.
Contemporary evangelicals and the doctrine of the Trinity -- Getting things straight : the issues in contention -- What the Bible says about the Trinity and what it does not say -- The eternal subordination of the Son of God -- The Father and the Son divided or undivided in power and authority -- Differentiating the trinitarian persons -- The economic and immanent Trinity : correspondence yes, identity no -- Subordination and obedience in the theology of Karl Barth -- Conclusion.
Includes bibliographical references and index.
Keywords: Trinity -- History of doctrines; Evangelicalism